Promoting Children’s Spiritual Intelligence and Personality Development - Sri Wahyuningsih (Jurnal Penelitian, 2018)
This present study aims to explore the urgency of promoting the spiritual intelligence of children in a family setting and its implications for the children’s development. A qualitative descriptive design was employed in this study. Three female and two male lecturers of Institut Agama Islam Negeri (IAIN) Kudus were recruited in this research. The study used in-depth interviews to collect the data. The findings demonstrate that the lecturers enhanced their children with Islamic education to shape their spiritual awareness. This study also highlights a wide array of reasons for the urgency of fostering the children’s spiritual intelligence attempted by the lecturers. Firstly, this kind of intelligence constitutes the value and meaning of spirituality. Secondly, it represents the nature of faith (spirituality) for human beings. Lastly, spiritual intelligence reflects the meaning or core of the whole intelligence that plays a pivotal role in the basis for intelligence quotient (IQ) and emotional quotient (EQ). The internalization of spiritual intelligence in children can be fostered when they are in the womb until adulthood through habituation, good modeling, and consistency from their parents. Furthermore, the implications of spiritual intelligence for children cover their character, emotional, psychological, and physical development.